A New Era of Foreign Investment Law and Policy? The Crisis of the Classic Theory and the Challenge of Regulation - Koutzoukou, Ioanna (Kent Law Review, 2014)
This article asks whether and to what extent successive economic crises, including the one which started in 2007, have weakened the hold of the classic approach to foreign investment in the field of foreign investment regulation. It explores this quesiton taking into account the apparent shift towards a multipolar world signalled by the emergence of the BRICS countries. It argues that the decline of the post-war superpower coupled with the absence of its replacement in a multipolar world order has prevented the emergence and implementation of a much needed new theoretical approach to foreign investment able to replace the classic theory.